2014
DOI: 10.1038/cddis.2013.519
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK/PTEN signaling is involved in AT-101-mediated apoptosis in human leukemia cells in vitro and in vivo

Abstract: R-(−)-gossypol acetic acid (AT-101) is a natural cottonseed product that exhibits anticancer activity. However, the molecular mechanism behind the antileukemic activity of AT-101 has not been well characterized. In this study, we investigated how AT-101 induces apoptosis in human leukemia cells. Exposure to AT-101 significantly increased apoptosis in both human leukemia cell lines and primary human leukemia cells. This increase was accompanied by the activation of caspases, cytochrome c release, Bcl2-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
(68 reference statements)
2
24
0
Order By: Relevance
“…Therefore it has been speculated that the formation of prostate carcinoma may be associated with overexpression of RhoA (30,31). The present study observed that prostate cells expressed ROCK/PTEN protein, and the expression of ROCK/PTEN protein in prostate carcinoma is also higher than that in BPH.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Therefore it has been speculated that the formation of prostate carcinoma may be associated with overexpression of RhoA (30,31). The present study observed that prostate cells expressed ROCK/PTEN protein, and the expression of ROCK/PTEN protein in prostate carcinoma is also higher than that in BPH.…”
Section: Discussionsupporting
confidence: 51%
“…The present study observed that prostate cells expressed ROCK/PTEN protein, and the expression of ROCK/PTEN protein in prostate carcinoma is also higher than that in BPH. Furthermore, the expression level of RhoA and ROCK/PTEN protein demonstrates significant positive correlation (30,31). These findings indicated that the ROCK/PTEN signal transduction pathway may participate in the occurrence of prostate carcinoma, and the expression level of ROCK/PTEN protein may be regulated and controlled by RhoA (32).…”
Section: Discussionmentioning
confidence: 97%
“…These studies demonstrate that the RhoA/ROCK signaling pathway may have regulatory roles on Runx2 expression in osteoblasts and suggests that the pathway may also have a role in regulating Runx2 expression in odontoblast differentiation. In the present study, the RhoA/ROCK signaling pathway inhibitor, C3 exoenzyme (37), was used to analyze the impact of the signaling pathway in hDPSCs. Results demonstrated that C3 exoenzyme treatment significantly downregulated the protein expression levels of RhoA, ROCK and Runx2 in hDPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…TNF‐a and IL‐1b induced Gluc secretion of 3T3‐L1‐NF‐kB‐RE‐GLuc adipocytes. Carnosic acid strongly suppressed GLuc secretion induced by macrophages and on the contrary up‐regulated adiponectin secretion on 3T3‐L1‐NF‐kB‐RE‐GLuc adipocytes . CA reduced expression of IL‐1b, and TNF‐a selectively inhibited COX‐2 of inflammation‐associated genes and significantly inhibited the overproduction of nitric oxide (NO) in a dose‐dependent manner in a macrophage cell line .…”
Section: Discussionmentioning
confidence: 99%